HIPERTENSI DI WILAYAH KERJA PUSKESMAS WONOBOYO TEMANGGUNG - Abdullah Azam Mustajab; Hety Sulistyowati; Marwiati Marwiati (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2023)
The shift in disease epidemiology which was originally an infectious disease has now shifted to non-communicable diseases which dominate morbidity and mortality in the world. One of the non-communicable diseases that is of concern and a global problem is hypertension. There are several risk factors for someone to get hypertension, both factors that can be changed and those that cannot be changed. The purpose of this study is to explain hypertension in the work area of the Wonoboyo Health Center, Temanggung. The research method uses observational analytic quantitative studies by observing secondary data with a total sample of patients who are detected as suffering from hypertension. The results showed that there were 3,734 (52.49%) female hypertension sufferers, 3,419 (48.06%) aged ≥61 years old hypertension sufferers, 5,862 (82.40%) grade 1 hypertension sufferers and 1,873 patients receiving treatment ( 26.33%). In conclusion, the causes of hypertension include excessive salt consumption, obesity, physical activity and exercise, smoking habits, alcohol consumption, age and gender and family history.